2016
DOI: 10.4271/2016-01-1456
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian/Bicyclist Limb Motion Analysis from 110-Car TASI Video Data for Autonomous Emergency Braking Testing Surrogate Development

Abstract: Many vehicles are currently equipped with active safety systems that can detect vulnerable road users like pedestrians and bicyclists, to mitigate associated conflicts with vehicles. With the advancements in technologies and algorithms, detailed motions of these targets, especially the limb motions, are being considered for improving the efficiency and reliability of object detection. Thus, it becomes important to understand these limb motions to support the design and evaluation of many vehicular safety syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…We tested 346 videos from JAAD database [23] and some pedestrian videos from TASI naturalistic database [25] [26] [27]. We analyze data manually by separating videos into different categories.…”
Section: Results Analysismentioning
confidence: 99%
“…We tested 346 videos from JAAD database [23] and some pedestrian videos from TASI naturalistic database [25] [26] [27]. We analyze data manually by separating videos into different categories.…”
Section: Results Analysismentioning
confidence: 99%
“…Euro NCAP has adopted the bicyclist surrogate with fixed leg posture (both legs bent) based on their study that suggests that a majority of bicyclists (over 80 per cent) stop pedaling when crossing an intersection in Europe. By examining 484 randomly selected bicyclist video clips in the TASI 110-car NDD (Sherony et al, 2016), it is observed that 83.2 per cent of bicyclists have pedaling motion when crossing the road, and 100 per cent of bicyclists have pedaling motion when moving along the road. The average pedaling frequency is 0.85 Hz for the cases of crossing the road (CP:VDO and CP:VS-BRO) and 1.01 Hz for the cases of moving along the road (PP-VOT and PP-VHO).…”
Section: Limb Motion Of the Bicycle Ridermentioning
confidence: 99%
“…La caracterización del comportamiento del peatón ha sido estudiada desde el punto de vista de la predicción de la trayectoria y del tipo de reacción de este [3], utilizando filtros de tipo Kalman para el análisis de imagen, mientras que otros autores [4] se centran en el desarrollo de modelos de decisión de tipo Markov (Markov decision process, MDP) para el desarrollo y mejora de los sistemas de frenado de emergencia y vehículos autónomos. Otros estudios [5], centran su investigación en la comprensión y el análisis del movimiento de las extremidades del peatón en función de la decisión de cruzar.…”
Section: Introductionunclassified